Effect of Shikonin on the Uterine Pathological Changes in Uterine Myoma Mice by Suppressing the Activation of MAPK/ERK Pathway - Jianhua Wang (Journal of Animal and Plant Sciences, 2025)
Uterine myoma (UM) is a benign tumor primarily characterized by clonal proliferation of uterine smooth muscle (USM) cells, with contributions from genetic and hormonal factors, and exhibits a high incidence rate. Shikonin (SHK), a bioactive naphthoquinone derived from Lithospermum erythrorhizon, exhibits potent anti-inflammatory and antitumor properties. This work investigated the effects of SHK on the uterine pathological conditions in UM mice and analyzed its potential mechanism of anti-UM activity based on the Mitogen-Activated Protein Kinase/Extracellular Signal-Regulated Kinase (MAPK/ERK) pathway. Thirty-six female ICR mice were randomly divided into six groups: Blank control group (BC group), UM model group (UM group), Positive control group (PC group), Low-dose SHK group (Low-SHK group), Middle-dose SHK group (Middle-SHK group), and High-dose SHK group (High-SHK group), with six mice in each group. The UM model was induced byintramuscular injection of estradiol benzoate for 15 consecutive days, andthe validity of the model was confirmed through uterine tissue histopathology (thickening of the smooth muscle layer and infiltration of inflammatory cells) and serum hormone levels (significant elevation of estradiol and progesterone)), Positive control group (PC group; continuous gavage of 0.1 μg/g estradiol valerate after modeling, Low-dose SHK group (Low-SHK group; continuous gavage of 100 μg/g SHKafter modeling), Middle-dose SHK group (Middle-SHK group; continuous gavage of 200 μg/g SHKafter modeling) and High-dose SHK group(High-SHK group; continuous gavage of 400 μg/g SHKafter modeling), with six mice in each. Blood was collected from the heart to detect serum sex hormone levels, and the uterus was taken after death. Hematoxylin-eosin staining was used to observe the pathological changes in the tissue. Real-time fluorescent quantitative PCR and Western blottingwere adopted to detect the distinctions in the expression of apoptosis-related mRNA [Bax, Bcl-2, and Caspase-3 (Cas-3)] and MAPK/ERK pathway-related proteins (p38 MAPK and ERK) in the uterus. As against BC group, in UM group, the weight of the uterus, the vertical/horizontal diameter, the organ coefficient, and the thickness of the smooth muscleall increased; the arrangement of USM cells was disordered, and there was inflammatory cell infiltration; the levels of serum estradiol, progesterone, luteinizing hormone, estrogen receptor, progesterone receptor, and follicle-stimulating hormone all increased, while the level of anti-Müllerian hormone (AMH) decreased; the expressionof Bax and Cas-3 in the uterus decreased, while the expression of Bcl-2 increased; the phosphorylation levels of p38 MAPK and ERKin the uterus increased (P ≤ 0.05). As against UM group, in PC group, Low-SHK group, Middle-SHK group and High-SHK group, the weight of the uterus, the vertical/horizontal diameter, the organ coefficient, and the thickness of the smooth muscle all decreased; the pathological changes in the uterus were alleviated; serum estradiol, progesterone, luteinizing hormone, estrogen receptor, progesterone receptor, and follicle-stimulating hormone all decreased, while AMH increased; the expressionof Bax and Cas-3 in the uterus increased, while the expressionof Bcl-2 decreased; the phosphorylation levels of p38 MAPK and ERKin the uterus decreased (P ≤ 0.05). With the increase of SHK dosage, the changes in the morphology of the uterus, the histopathological morphology, the serum sex hormones, the expression of apoptosis-related mRNA in the uterus, and the expression of MAPK/ERK pathway-related proteins became more obvious (P ≤ 0.05). SHK suppressed UM progression by reducing uterine weight, vertical/horizontal diameters, and smooth muscle thickness, while restoring serum sex hormone balance and promoting apoptosis via Bax/Cas-3 upregulation and Bcl-2 downregulation. These effects were mediated through dose-dependent inhibition of MAPK/ERK pathway activation.
Keywords: Uterine myoma; Shikonin; uterine morphology; sex hormones; apoptosis; MAPK/ERK pathway